Performing the Cold War in the Postcolonial World Theatre, Film, Literature and Things - Balme, Christopher B. (Routledge Studies in Cultures of the Global Cold War, 2024)
Cultural Cold War, decolonization, postcolonial studies, cultural diplomacy, national theatre